A novel method of studying the collapsed cell of eucalyptus wood using X-ray CT scanning. Issue 12 (10th September 2019) - Yang, Lin; Liu, Honghai; Cai, Yingchun; Wu, Zhihui
Abstract: Collapse is the severest defect for collapse-prone species used as solid wood product materials. Previous study focused on the morphological structures by scanning electron microscopy (SEM) to observe the change of the collapsed cells during the drying processes. The multi planar reconstruction by X-ray computed tomography (CT) scanning provided a new method for cell microstructure observation. In this study, cell collapse of Eucalyptus urophylla were observed by SEM and X-ray CT scanning during the continuous and intermittent drying process. The cell shapes, cell types, cell collapsed quantities and the shrinkage curves were determined. The results demonstrated that layered scanning technique by X-ray CT scanning provided a top-down approach to investigate the structure in depth at different layers in a fast and nondestructive way. Compared with SEM observation, this approach emphasized more specific aspects and information for collapse quantitative analysis. Quantitative analysis of collapsed cells by X-ray CT scanning not only indicated the cell deformation but quantified the extent of cells collapse. The shrinkage rate was also measured by calculating the areas change in porosity at tissue level before and after drying through X-ray CT scanning. It indicates that intermittent drying process may decrease the extent of cell collapse or accelerate the recovery of collapsed cells. These results further confirm that the X-ray CT scanning provides another effective method for wood cell collapse study at the morphological level.